RETRACTED: Targeting and Therapy of Glioblastoma in a Mouse Model Using Exosomes Derived From Natural Killer Cells - Zhu, Liya; Oh, Ji Min; Gangadaran, Prakash; Kalimuthu, Senthilkumar; Baek, Se Hwan; Jeong, Shin Young; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol (Frontiers in Immunology, 2018)
Objective: Glioblastoma is a highly aggressive primary brain tumor that is resistant to radiotherapy and chemotherapy. Natural killer (NK) cells have been used to treat incurable cancers. Recent studies investigated the effectiveness of NK-cell-derived exosomes (NK-Exo) for treating incurable cancers, such as melanoma, leukemia, and neuroblastoma; however, NK-Exo have not been used for treating glioblastoma. In the present study, we investigated the antitumor effects of NK-Exo against aggressive glioblastoma both in vitro and in vivo and determined the tumor-targeting ability of NK-Exo by performing fluorescence imaging. Methods: NK-Exo were isolated by ultracentrifugation, purified by density gradient centrifugation, and characterized by TEM, DLS, NTA, and western blotting. Cytokine levels in NK-Exo were compared with those in NK cells and NK-cell medium by performing ELISA. NK-Exo-induced apoptosis of cancer cells was confirmed by flow cytometry and western blotting. In vivo therapeutic effects and specificity of NK-Exo against glioblastoma were assessed in xenograft mouse model by FLI. Xenograft mice were treated with NK-Exo, which was administered through the tail vein, seven times. Tumor growth was monitored by bioluminescence imaging, and tumor volume was measured by ultrasound imaging. The mice were intraperitoneally injected with dextran sulfate 2 h before NK-Exo injection to decrease liver uptake and increase the tumor specificity of NK-Exo. Results: NTA and DLS results indicated that the size of the NK-Exo was ~100 nm, and western blot results confirmed that NK-Exo expressed exosome markers CD63 and Alix. We confirmed the in vitro cytotoxic effects of NK-Exo on U87/MG/F cells by performing BLI, with the killing effect on U87/MG and U87MG/F cells measured by the CCK-8 and MTT assays. ELISA results indicated that NK-Exo contained tumor necrosis factor-α and granzyme B. In vivo NK-Exo treatment inhibited tumor growth as compared with that in control mice, and pretreatment of xenograft mice with with dextran sulfate 2 h before NK-Exo treatment increased the the antitumor effect of NK-Exo as compared with that observed in control and NK-Exo-alone-treated mice.Conclusion: These results indicated that NK-Exo targeted and exerted antitumor effects on glioblastoma cells both in vitro and in vivo, suggesting their utility in treating incurable glioblastoma.